Performance of bioreactor and pH meter instrument in bioethanol producing process from brown seaweed(Sargassum duplicatum) - Rodiah Nurbaya Sari; Diah Lestari Ayudiarti; Diini Fithriani (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2011)
To meet the energy needs this time we are still dependent on energy derived from fossilresources that can not be recovered (fossil energy). The way to tackle the energy problem is toexplore other energy resources namely biofuels, one of its kind is bioethanol. Source of potentiallyraw material from the sea is brown seaweed which cellulose content and stored carbohydrate(mannitol) is quite high. The use of a batch bioreactor and the pH meter instrument assembliesResearch Center for Marine and Fisheries Products Processing and Biotechnology (RCMFPPB)has been supporting the production of bioethanol with raw material brown seaweed Sargassumduplicatum.